Integration of Functional Imaging, Cytometry, and Unbiased Proteomics Reveals New Features of Endothelial-to-Mesenchymal Transition in Ischemic Mitral Valve Regurgitation in Human Patients - Lupieri, Adrien; Nagata, Yasufumi; Passos, Livia S. A.; Beker-Greene, Dakota; Kirkwood, Katherine A.; Wylie-Sears, Jill; Alvandi, Zahra; Higashi, Hideyuki; Hung, Judy W.; Singh, Sasha A.; Bischoff, Joyce; Levine, Robert A.; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Following myocardial infarction, mitral regurgitation (MR) is a common complication. Previous animal studies demonstrated the association of endothelial-to-mesenchymal transition (EndMT) with mitral valve (MV) remodeling. Nevertheless, little is known about how MV tissue responds to ischemic heart changes in humans. Methods: MVs were obtained by the Cardiothoracic Surgical Trials Network from 17 patients with ischemic mitral regurgitation (IMR). Echo-doppler imaging assessed MV function at time of resection. Cryosections of MVs were analyzed using a multi-faceted histology and immunofluorescence examination of cell populations. MVs were further analyzed using unbiased label-free proteomics. Echo-Doppler imaging, histo-cytometry measures and proteomic analysis were then integrated. Results: MVs from patients with greater MR exhibited proteomic changes associated with proteolysis-, inflammatory- and oxidative stress-related processes compared to MVs with less MR. Cryosections of MVs from patients with IMR displayed activated valvular interstitial cells (aVICs) and double positive CD31+ αSMA+ cells, a hallmark of EndMT. Univariable and multivariable association with echocardiography measures revealed a positive correlation of MR severity with both cellular and geometric changes (e.g., aVICs, EndMT, leaflet thickness, leaflet tenting). Finally, proteomic changes associated with EndMT showed gene-ontology enrichment in vesicle-, inflammatory- and oxidative stress-related processes. This discovery approach indicated new candidate proteins associated with EndMT regulation in IMR. Conclusion: We describe an atypical cellular composition and distinctive proteome of human MVs from patients with IMR, which highlighted new candidate proteins implicated in EndMT-related processes, associated with maladaptive MV fibrotic remodeling.